2011
DOI: 10.1093/icc/dtr022
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corporate governance practices on R&D efforts: a look at shareholders' rights, cross-listing, and control pyramid

Abstract: The article considers the impact of multiple shareholder-oriented governance practices on R&D decisions. Based on a sample of 5528 firms belonging to 110 large French listed business groups, our results substantiate the idea that shareholder-oriented governance practices and a lower position in a control pyramid are better for R&D investment. The introduction of any additional shareholder oriented practice is found to result in more R&D. We show, however, that this Anglo-Americanization of the French corporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 96 publications
(82 reference statements)
2
53
0
Order By: Relevance
“…In recent papers, it has been suggested that further progress may depend on integrating the theory of R&D investment with models of agency and financial constraints (Hall 2002;O'Sullivan 2005;Lhuillery 2011). …”
Section: Theories Of Randd Investmentmentioning
confidence: 99%
“…In recent papers, it has been suggested that further progress may depend on integrating the theory of R&D investment with models of agency and financial constraints (Hall 2002;O'Sullivan 2005;Lhuillery 2011). …”
Section: Theories Of Randd Investmentmentioning
confidence: 99%
“…A detailed set of corporate governance provisions are analysed, rather than one single dimension, which allows the taking into account of several dimensions simultaneously. The focus on practices affecting the relationships between managers and shareholders allows the testing of the basic premises of agency theory, with respect to R&D. The paper provides empirical evidence on a multi-country sample of companies, thus complementing previous studies, which focused on single countries, such as France (Lhuillery, 2011), the United Kingdom (Driver and Coelho Guedes, 2012) or the United States (Becker-Blease, 2011). Addressing these issues is important because policies designed to improve shareholders' protection might actually have a negative impact on flexibility and risktaking, as evidenced by recent studies on the consequences of the Sarbanes-Oxley Act in the United States (Bargeron et al, 2010;Cohen et al, 2009).…”
Section: Introductionmentioning
confidence: 88%
“…Initial empirical contributions have analysed the impact on R&D intensity of the degree of ownership concentration (Lee and O'Neil, 2003;Tribo et al, 2007), owner identity (Hoskisson et al, 2002;Kim et al, 2008;Munari et al, 2010) or the role and composition of the board of directors (Kor, 2006). More recent contributions have investigated the role of corporate governance practices, such as compensation schemes for CEOs, managers and directors (Barker and Mueller, 2002;Coles et al, 2006;Hoskisson et al, 2002), power separation between managers and board members (Driver and Coelho Guedes, 2012), and annual shareholders' meeting rules (Lhuillery, 2011). The advantage of these later constructs is that they reflect actual practices that have been designed and carried out within companies rather than board or shareholder compositions that might exist for historical reasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we focus on small and medium sized groups which are less 1 This is the same definition normally adopted in the economics and business literature (Lhuillery, 2011). The definition of business group used in this paper is also the one normally adopted by statistical agencies (Eurostat 2003) and by the financial accounting standards for delimiting the area of consolidation when drawing consolidated financial statements.…”
mentioning
confidence: 99%